Hubungan Konsumsi Fast Food Dengan Siklus Menstruasi Pada Remaja Di SMA Negeri 1 - Nurlela Hi Baco; Sun Kalsum Windah Alitu; Kristine Dareda (Akademi Keperawatan Yarsi Samarinda, 2026)
Adolescents’ fast food consumption has increased in line with lifestyle changes favoring practical, accessible, and flavorful meals. Excessive consumption may negatively affect health, including female reproductive function, such as menstrual cycle irregularities. Diets high in fat, sugar, and sodium can disrupt hormonal balance, particularly estrogen and progesterone, which regulate the menstrual cycle. The objective of this research was to examine the relationship between fast food consumption and menstrual cycle patterns among adolescents at SMA Negeri 1 Manado. Purpose. This study employed a quantitative cross-sectional design. a sample of 64 respondents selected using purposive sampling. Data were collected using the Food Frequency Questionnaire (FFQ) and a menstrual cycle questionnaire. Analysis was conducted using univariate methods to describe characteristics and bivariate analysis with the Chi-Square test to assess relationships between variables.Methods. The findings revealed that most respondents frequently consumed fast food (52.8%), while the majority reported normal menstrual cycles (54.7%). Chi-Square analysis produced a ρ-value of 0.000 (ρ < 0.05), indicating a significant relationship between fast food consumption and menstrual cycle patterns among adolescents Result. The study concludes that fast food consumption is significantly associated with menstrual cycle regularity among adolescents at SMA Negeri 1 Manado. It is recommended that adolescents adopt healthier and more balanced dietary patterns to maintain reproductive health and menstrual cycle regularity.